All Days 2009
DOI: 10.2118/127549-ms
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Logging in Russia: Development History of Theory, Technology of Measurements and Interpretation Techniques

Abstract: The history of development and the state of the art of well temperature logging in Russia is described in the paper. As it is known, the first logging in oil wells were temperature ones. In 1906 D. Golubyatnikov made the first measurement of temperature distribution along the well bore using the maximal thermometer. In 1932 it was developed the first electronic well thermometer. From 1970 in practice of field reserarches the high sensitive thermometers with resolution of 0.01K are used: it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
2
5
0
1
Order By: Relevance
“…(Bahrami and Siavoshi 2007) observed transient, sandface temperature behavior and noted that the "temperature jump" caused by the transient fluid expansion/compression effect at the beginning of a transient flow period may provide valuable information, providing it is not masked by the wellbore storage effects. These "jumps" (or "barothermal effects") were observed by (Valiullin et al 2009) in experimental wells and in the simulation results similar to (Zhu et al 2008). (Valiullin et al 2009) highlighted the value of temperature transient analysis, particularly if the barothermal effect was observed, for well-test analysis purposes.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…(Bahrami and Siavoshi 2007) observed transient, sandface temperature behavior and noted that the "temperature jump" caused by the transient fluid expansion/compression effect at the beginning of a transient flow period may provide valuable information, providing it is not masked by the wellbore storage effects. These "jumps" (or "barothermal effects") were observed by (Valiullin et al 2009) in experimental wells and in the simulation results similar to (Zhu et al 2008). (Valiullin et al 2009) highlighted the value of temperature transient analysis, particularly if the barothermal effect was observed, for well-test analysis purposes.…”
supporting
confidence: 82%
“…These "jumps" (or "barothermal effects") were observed by (Valiullin et al 2009) in experimental wells and in the simulation results similar to (Zhu et al 2008). (Valiullin et al 2009) highlighted the value of temperature transient analysis, particularly if the barothermal effect was observed, for well-test analysis purposes. They also provided an integral solution for the radial flow problem that ignored heat conduction.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The advances in downhole monitoring systems in recent years have motivated new testing and analysis techniques. Valiullin highlighted the importance of Temperature Transient Analysis (TTA) especially when the barothermal effect (transient fluid compression/expansion at early times) takes place for well test analysis (Valiullin, Ramazanov et al 2009). They indicated that trasient temperature can be more informative than pressure due to its sensitivity to damage radius and permeability.…”
mentioning
confidence: 99%